Peperangan Proxy, Mozarab, dan Cordova Dalam Sejarah Umayyah II Di Andalusia - Muhammad Affan (UIN Sumatera Utara Medan, 2018)
AbstractThe following article aims to describe the proxy warfare, Mozarab and city of Cordova in the history of Umayyad II in Andalusia, Spain. The results of the study are expected to contribute historical-based thinking in the development of Islamic studies and social-humanities studies. The method used in this study is the method of historical research through literature review. From the study, it is concluded that Umayyad II prefers to align with the Byzantine on the basis of the political interests of power rather than the fraternal brethren of Muslims. Umayyad II is also more oriented towards Arabization than the Islamization of the Andalusian region as evidenced by the emergence of the Mozarab social class and the highly civilized city of Cordova. So it can be understood further that the presence of Umayyad II rule in Andalusia is not a direct cause of the spread of Islam in the region.Keywords: proxy warfare, Mozarab, Cordova, Umayyad Andalusia IntisariArtikel berikut bertujuan untuk menguraikan peperangan proxy, mozarab dan kota Cordova dalam sejarah Umayyah II di Andalusia, Spanyol. Hasil kajian diharapkan dapat memberi sumbangan pemikiran berbasis sejarah dalam pengembangan studi-studi Islam dan studi sosial humaniora. Metode yang dipergunakan dalam kajian adalah metode penelitian sejarah melalui kajian literatur. Dari kajian yang dilakukan, diperoleh kesimpulan bahwa Umayyah II lebih memilih beraliansi dengan Byzantine atas dasar kepentingan politik kekuasaan ketimbang persaudaraan sesama Muslim. Umayyah II juga lebih berorientasi pada usaha arabisasi daripada islamisasi wilayah Andalusia yang dibuktikan dengan kemunculan kelas sosial mozarab dan kota Cordova yang berperadaban tinggi. Sehingga dapat difahami lebih jauh bahwa kehadiran kekuasaan Umayyah II di Andalusia tidak menjadi sebab langsung penyebaran agama Islam di wilayah tersebut.Kata kunci: peperangan proxy, mozarab, cordova, Umayyah Andalusia